2002
DOI: 10.1002/hrdq.1042
|View full text |Cite
|
Sign up to set email alerts
|

The relative impact of workplace design on training transfer

Abstract: The multidimensional nature of training transfer presents a formidable challenge to organizations. Corporate America has continued to spend billions of dollars annually on training, yet much of it either failed to transfer or has been extinguished over time (Broad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 31 publications
5
72
0
1
Order By: Relevance
“…Many studies have focused on various aspects of transfer of training and some of them have provided evidence of low transfer (e.g., Baldwin & Ford, 1988;Kupritz, 2002).Therefore, it becomes necessary to identify factors which ensure transfer of training at a higher level. Scholars agree that the problem of transfer is related to training design, trainee characteristics, and the organizational characteristics (Cheng & Hampson, 2008).…”
Section: S Singhmentioning
confidence: 99%
“…Many studies have focused on various aspects of transfer of training and some of them have provided evidence of low transfer (e.g., Baldwin & Ford, 1988;Kupritz, 2002).Therefore, it becomes necessary to identify factors which ensure transfer of training at a higher level. Scholars agree that the problem of transfer is related to training design, trainee characteristics, and the organizational characteristics (Cheng & Hampson, 2008).…”
Section: S Singhmentioning
confidence: 99%
“…Anonymous, 1998;Bencivenga, 1998;Grossman, 2002;Hays, 1998;Khanna & New, 2008;Poe, 2000;Sunoo, 2000;Thomas, 2005). Common changes include introducing open plan offices, cubicles and ergonomic furniture and have led to increased worker performance and satisfaction (Bencivenga, 1998;Brockbank, 1999;Grossman, 2002;Khanna & New, 2008;Kupritz, 2002;May, Oldham, & Rathert, 2005;Vanarsdall, 2005), improved communication and teamwork (Brockbank, 1999;May, 2008), better transfer to the job of learned skills (Kupritz, 2002), and better recruitment and retention of qualified personnel (Earle, 2003;Hays, 1998). HRM involvement in major changes in office spaces in Continental Europe have been reported, for example, in companies in Sweden (Edvinsson, 1997), Denmark (Koch, 2003), and in the Netherlands (Hogenes, Dul & Haan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the ultimate goal of training should be positively transferred into the workplace (Berry & Morris, 2005). Unfortunately, research revealed there is only a lower percentage of learning actually transferred into job performance (Holton & Baldwin, 2000 ;Kupritz, 2002). Training transfer (TT) is an important concern for training researchers and practitioners due to it being estimated that only a small percentage of the training actually results in transfer to the job (Baldwin & Ford, 1988).…”
Section: Introductionmentioning
confidence: 99%